IgG4-Related Disease With Gastrointestinal Involvement: Case Reports and Literature Review - Zhang, Xinhe; Jin, Xing; Guan, Lin; Lin, Xuyong; Li, Xuedan; Li, Yiling (Frontiers in Immunology, 2022)
IgG4-related disease is an immune-mediated chronic, systemic, and autoinflammatory disease that can affect various organs throughout the body. The most commonly affected areas are the pancreas and biliary system. Due to the diverse clinical manifestations of the disease, it affects widely distributed organs. Thus, it is often easy to misdiagnose or miss. The digestive tract is rarely affected system, and most IgG4-related gastric diseases manifest as tumors detected by endoscopy. This article reports two special cases with IgG4-related disease involving atrophic gastritis and intestinal polyps to provide a more empirical and theoretical basis for clinical diagnosis and treatment.